2012
DOI: 10.1021/cs300045r
|View full text |Cite
|
Sign up to set email alerts
|

An in Situ NMR Study of the Mechanism for the Catalytic Conversion of Fructose to 5-Hydroxymethylfurfural and then to Levulinic Acid Using 13C Labeled d-Fructose

Abstract: The pathways for the formation of 5-hydroxymethylfurfural (HMF) by dehydration of D-fructose and for the formation of levulinic acid and formic acid from HMF by rehydration were investigated by in situ 13 C and 1 H NMR using both unlabeled and 13 C-labeled fructose. Water or DMSO was used as the solvent with Amberlyst 70, PO 4 3− / niobic acid, or sulfuric acid as catalysts. Only HMF is observed using NMR for fructose dehydration in DMSO with any of the three catalysts or without a catalyst. For each system, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 50 publications
9
104
0
3
Order By: Relevance
“…A similar study reported for DMSO and H 2 O has verified that the C 1 -and C 6 -carbons of D-fructose appears at the corresponding position in 5-HMF [144], which was transferred into the formic acid and the carboxyl group of the levulinic acid, as expected (Scheme 16).…”
Section: Fundamental Reactions Involving Watersupporting
confidence: 80%
“…A similar study reported for DMSO and H 2 O has verified that the C 1 -and C 6 -carbons of D-fructose appears at the corresponding position in 5-HMF [144], which was transferred into the formic acid and the carboxyl group of the levulinic acid, as expected (Scheme 16).…”
Section: Fundamental Reactions Involving Watersupporting
confidence: 80%
“…Notably, the deuterium atom from HMF was transferred onto formic acid and not onto levulinic acid, which indicated that the rehydration of HMF involved 1,2-CÀC bond breaking to form formic and levulinic acids, as also indicated in a recent study. [23] As demonstrated herein, the mapping of hydrogen atoms from the reactants to the products or intermediates can assist in the development of mechanisms for the dehydration and rehydration reactions in biomass-derived molecules.…”
Section: H Nmr Investigations Of the Crcl 3 -Catalyzed Glucose Transfmentioning
confidence: 95%
“…The optimum temperature was found to be 200-220°C. [31,46,47,160]. The amount of water solvent can affect the hydrolysis process and the optimal concentration was found to be *90 wt%.…”
Section: Homogeneous Acid Catalysismentioning
confidence: 99%